2016
DOI: 10.1002/rcm.7753
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of alteration of serum IgG in patients with schizophrenia after risperidone treatment by matrix‐assisted laser desorption ionization/time‐of‐flight mass spectrometry

Abstract: This study found that applying acid hydrolysis with MALDI-TOF MS technology could rapidly differentiate serum IgG levels in patients with schizophrenia before and after being treated with risperidone. This IgG difference may enhance the understanding of mechanism of antipsychotic treatment of schizophrenia. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…During 6 months of risperidone treatment (2-6 mg/day), TNF-α levels increased compared with baseline while IL-1β and IL-6 decreased at 1 month and then gradually increased at the end of the follow-up (154). In ASD patients, eotaxin and monocyte chemoattractant protein-1 (MCP-1) levels significantly decreased after 8 weeks of treatment (0.5-1.5 mg/day) (177). Regarding Igs, a report showed that a 4-week treatment with risperidone increased Igγ (IgG) chain levels significantly when compared with baseline (178).…”
Section: Risperidonementioning
confidence: 99%
“…During 6 months of risperidone treatment (2-6 mg/day), TNF-α levels increased compared with baseline while IL-1β and IL-6 decreased at 1 month and then gradually increased at the end of the follow-up (154). In ASD patients, eotaxin and monocyte chemoattractant protein-1 (MCP-1) levels significantly decreased after 8 weeks of treatment (0.5-1.5 mg/day) (177). Regarding Igs, a report showed that a 4-week treatment with risperidone increased Igγ (IgG) chain levels significantly when compared with baseline (178).…”
Section: Risperidonementioning
confidence: 99%
“…Yet another report described a decreased IgD levels in BD [ 35 ]. Studies focusing on SZ revealed an elevation of IgA, IgM or IgG in the patients’ sera or CSF during acute phases of the disease ([ 1 , 3 , 6 , 10 , 11 , 16 , 27 , 29 , 32 ]). Interestingly, in SZ, IgG raises gradually to reach a peak at about 12 to 17 years after the onset typically mirroring persistence of an underlying infection [ 10 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, trifluoroacetic acid was used to effectively hydrolyze albumin, and a decrease was observed in the ion ratio of transferrin to fibrinogen fragments in the sera of patients diagnosed with acute-phase mental disorders [ 20 ]. Another analytical strategy involving strong acid hydrolysis followed by off-line HPLC coupled with MALDI-TOF analysis was able to characterize serum IgG levels in schizophrenia patients before and after risperidone treatment [ 21 ].…”
Section: Introductionmentioning
confidence: 99%